(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
In this article, we will talk about the autumn nightshade from root rodent tunlams in the potato field (Agrotis segetum Den. et Schiff) and exclamation points (Agrotis exclamationis Den. spread, harm and anti-Telecha 20% k of et Schiff).e. and Ampligo 150 m.k.shut up. in order to determine the effectiveness of their chemical preparations, research was carried out on the farm "Faradis khirmoni" in Upper Chirchik District of Tashkent region and conclusions and suggestions were made based on the results obtained